2001
DOI: 10.3341/kjo.2001.15.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual field defects between primary open-angle glaucoma and chronic primary angle-closure glaucoma in the early or moderate stage of the disease

Abstract: The visual field data (Humphrey C24-2) of early to moderate stage glaucoma between primary open-angle glaucoma (POAG) and chronic primary angle-closure glaucoma (PACG) patients was compared. Eleven POAG (11 eyes) and 14 chronic PACG patients (14 eyes) were matched with respect to age, sex, and disease severity. Although the mean deviation, pattern standard deviation, and short-term fluctuation were similar between the two groups, the mean corrected pattern standard deviation was higher in the POAG patients (p=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 0 publications
6
32
0
Order By: Relevance
“…10,11 In a small study of eyes with POAG and PACG controlled for age, sex, and disease severity, Rhee et al 11 compared global perimetric indices in early and moderate stages of disease. Interestingly, CPSD was significantly higher in their POAG group, suggesting a difference in pattern of field loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 In a small study of eyes with POAG and PACG controlled for age, sex, and disease severity, Rhee et al 11 compared global perimetric indices in early and moderate stages of disease. Interestingly, CPSD was significantly higher in their POAG group, suggesting a difference in pattern of field loss.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were: (1) age less than 30 years, (2) women who may be pregnant at time of surgery, (3) cataract that may require surgery within 3 years, (4) previous intraocular or conjunctival surgery, (5) treatment with warfarin, (6) a history of uveitis, (7) any neovascularisation, or (8) epithelial in-growth, (9) chronic use of topical or systemic steroids, (10) previous chemotherapy, or (11) other systemic pathology that might result in a visual field defect.…”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective study of 102 glaucoma patients followed for 15yrs,Eid and colleagues 17 found 29% paracentral scotoma, 20% nasal steps and18% arcuate scotomas as predominant field defects however in this study arcuate scotoma was the most common defect (28.87%). K. Rhee & Young Kim 18 found more depressed paracentral points were found in POAG patients. Out of 29 cases of secondary glaucoma 15(51.72%) patients had lens induced glaucoma.This included glaucoma due to pupillary block associated with intumescent or hypermature morgagnian cataract, phacolytic glaucoma, phacotoxic glaucoma and secondary glaucoma associated with displacement of lens.…”
Section: Discussion:-mentioning
confidence: 92%
“…Current theories postulate a mixed mechanism of optic nerve damage in POAG, with elements of pressure-sensitive and pressureindependent damage responsible for the characteristic patterns of glaucomatous optic neuropathy 6 . It is likely that PACG is a more pressure-dependent disease, said Ritch 9 .There was no significant asymmetry in the nasal fields. The possible reason could be more universal vulnerability of these nerve fibre layers during early phases in each disease, or a lack of sensitivity of AGIS scoring techniques to detect subtle differences in nasal field loss 6 .…”
Section: Discussionmentioning
confidence: 99%
“…However, another study by Wang et al 4 had a predominance of male patients in the POAG group (3:1) as compared with almost equal representation in the PACG group. In a study by Rhee et al 9 , the maximum IOPs were higher in PACG group (31.9mm Hg) vs POAG group (25.1 mmHg) and the mean IOP at the time of visual fields test was higher in the POAG group (22.5 +/-4.8 mmHg) vs PACG group (17.2 +/-5.5 mmHg).In our study, the mean IOP at the time of diagnosis, in the PACG group was higher being 30.06 +/-0.5, while the mean IOP in the POAG group was 27.05 +/-0.5mmHg.Caprioli et al 10 reported that IOPs were consistently higher in eyes with diffuse field loss compared to eyes with localised field loss. Rhee et al 9 , showed a statistically higher PSD and CPSD in POAG group than in PACG patients, suggesting that PACG patients had a more diffuse field loss than PACG patients, as a higher PSD indicates an irregular hill in the field of vision.…”
Section: Discussionmentioning
confidence: 99%